Workshop Penerapan Lesson Study untuk Mengembangkan Budaya Refleksi pada Implementasi Kurikulum Merdeka - Suryani, Yeyen; Jumantini, Entin; Djuniardi, Dede; Pratiwi, Rani Tania; Mulyati, Sri (Kreativasi : Journal of Community Empowerment, 2024)
The Workshop on the Application of Lesson Study to Develop a Culture of Reflection in the Implementation of the Independent Curriculum aims to introduce and promote the practice of Lesson Study as a tool to improve the quality of learning in schools implementing the Independent Curriculum. The Independent Curriculum was introduced as an effort to provide schools with the freedom to develop curricula that align with local needs and the characteristics of their students. Its urgency lies in the need to adapt effective and relevant teaching approaches to the current educational context. A culture of reflection is key to improving the quality of teaching practices. Through Lesson Study, educators can collaborate, plan, observe, and reflect on their teaching practices regularly. The goal of this workshop is to enhance educators' understanding and skills in applying Lesson Study as a systematic approach to teacher professional development and improving student learning outcomes. The workshop also aims to strengthen the culture of collaboration and reflection among educators so that they can effectively implement the Independent Curriculum while taking into account students' needs and contexts. The targeted outcomes of this workshop include improving teachers' skills in planning, implementing, and evaluating the teaching process through Lesson Study. Thus, this workshop successfully provides teachers with a better understanding of the importance of applying Lesson Study to build a culture of reflection in teaching, particularly in the context of implementing the Independent Curriculum.